ENHANCING STUDENTS’ READING COMPREHENSION OF RECOUNT TEXT WITH MULTIMODAL DIGITAL LITERACY - Siti Mariam; Catur Kepirianto; Sayyidatul Fadlilah; Awwalia Fitrotin Izza (University of Kuningan, 2025)
This study aims firstly to explain the use of multimodal digital literacy to boost students’ reading comprehension of recount text. Secondly, to describe students’ engagement in joining this learning model. It employed a qualitative method. Classroom action research with two cycles was used as the research design. Each cycle consisted of planning, acting, observing, and evaluating. The participants were thirty-ninth graders at the Islamic secondary school in Semarang Regency in the academic year 2024-2025. The pre-test, posttests, and observation guidelines were provided as data collection techniques. The results show that incorporating a genre-based approach and multimodal digital literacy can enhance students’ reading comprehension of recount text. Based on students’ achievement in the pretest, they reached 69, in post-test cycle 1, they achieved 75, and in post-test cycle 2, they obtained 84. Because students were intrigued by multimodal digital literacy, they were also delighted in putting this learning approach into practice. Their grasp of reading comprehension of recall texts was enhanced by the teacher. Together with their peers and the teacher, they studied the course materials. It can be concluded, this learning paradigm improves group work and interpersonal skills, raises learning motivation, and promotes active learners' involvement.Keywords: digital literacy, multimodal; reading comprehension; recount text; revolutionizing.